Bias and Its Consequences : A Study of Machine Learning Performance - Anirudh Kokate,; Madhu Priya, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper addresses the concern about bias affecting the results of machine learning models. For this purpose, it uses the Adult Income dataset from OpenML for income classification. The conditions for bias are induced by underrepresenting people that earn
Keywords: Machine Learning; Fairness in AI; Class imbalance and Bias Impact Analysis